Gene Therapy and Hemophilia: Where Do We Go from Here? - Bolous NS; Bhatt N; Bhakta N; Neufeld EJ; Davidoff AM; Reiss UM (Journal of Blood Medicine, 2022)
Nancy S Bolous,1 Nidhi Bhatt,2 Nickhill Bhakta,1 Ellis J Neufeld,2 Andrew M Davidoff,3 Ulrike M Reiss2 1Department of Global Pediatric Medicine – St. Jude Children’s Research Hospital, Memphis, TN, USA; 2Department of Hematology – St. Jude Children’s Research Hospital, Memphis, TN, USA; 3Department of Surgery – St. Jude Children’s Research Hospital, Memphis, TN, USACorrespondence: Nancy S Bolous, Department of Global Pediatric Medicine, St. Jude Children’s Research Hospital, 262 Danny Thomas Place, Mail Stop 721, Memphis, TN, 38105, USA, Tel +1 901 595 1968, Fax +1 901 595 5319, Email nancy.bolous@stjude.orgAbstract: Gene therapy for hemophilia using adeno-associated virus (AAV) derived vectors can reduce or eliminate patients’ disease-related complications and improve their quality of life. Broad implementation globally will lead to societal gains and foster health equity. Several vector products each for factor IX (FIX) or factor VIII (FVIII) deficiency are in advanced clinical development. Safety data are reassuring. Efficacy data for up to 8 and 5 years, respectively, vary considerably among vector types and among individuals, but indicate significant reduction in bleeds and factor use. Products will soon be approved for marketing. This review highlights the relevant considerations for implementation of hemophilia gene therapy, specifically across a broad range of socioeconomic backgrounds globally, based on recent publications and our own experience. We address the current efficacy and safety data and relevant aspects of vector immunology. We then discuss pertinent implementation steps including pre-implementation and readiness assessments, considerations on cost, cost-effectiveness and payment models, approaches to education and informed consent, and the operational needs as well as the need for monitoring of health outcomes and implementation outcomes. To prevent a lag or complete lack of establishing access to this life-changing therapy option for all patients with hemophilia worldwide, adaptable pathways supported by collaborative and international efforts of all stakeholders are needed.Keywords: global health, health equity, cost-effectiveness, adeno-associated virus vector, factor VIII, factor IX